Differential structural features in soleus and gastrocnemius of carnitine‐treated cancer cachectic rats. Issue 1 (26th June 2019) - Busquets, Sílvia; Pérez‐Peiró, Maria; Salazar‐Degracia, Anna; Argilés, Josep M.; Serpe, Roberto; Rojano‐Toimil, Alba; López‐Soriano, Francisco J.; Barreiro, Esther
Abstract: Muscle wasting is associated with chronic diseases and cancer. Elucidation of the biological mechanism involved in the process of muscle mass loss and cachexia may help identify therapeutic targets. We hypothesized that l ‐carnitine treatment may differentially revert muscle fiber atrophy and other structural alterations in slow‐ and fast‐twitch limb muscles of rats bearing the Yoshida ascites hepatoma. In soleus and gastrocnemius of tumor‐bearing rats (10 8 AH‐130 Yoshida ascites hepatoma cells inoculated intraperitoneally) with and without treatment with l ‐carnitine (1 g/kg body weight for 7 days, intragastric), food intake, body and muscle weights, fiber typing and morphometry, morphological features, redox balance, autophagy and proteolytic, and signaling markers were explored. Levels of carnitine palmitoyl transferase were also measured in all the study muscles. l ‐ Carnitine treatment ameliorated the atrophy of both slow‐ and fast‐twitch fibers (gastrocnemius particularly), muscle structural alterations (both muscles), and attenuated oxidative stress, proteolytic and signaling markers (gastrocnemius). Despite that carnitine palmitoyl transferase‐1 levels increased in both muscle types in a similar fashion, l ‐carnitine ameliorated muscle atrophy and proteolysis in a muscle‐specific manner in cancer‐induced cachexia. These data reveal the need to study muscles of different fiber type composition and function to better understand whereby l ‐carnitine exerts its beneficial effects on the myofibers in muscle wasting processes. These findings also have potential clinical implications, since combinations of various exercise and muscle training modalities with l ‐carnitine should be specifically targeted for the muscle groups to be trained. Abstract : Despite that carnitine palmitoyl transferase‐1 levels increased in both muscle types in a similar fashion, l ‐carnitine ameliorated muscle atrophy and proteolysis in a muscle‐specific manner in cancer‐induced cachexia. These data reveal the need to study muscles of different fiber type composition and function to better understand whereby l ‐carnitine exerts its beneficial effects on the myofibers in muscle wasting processes. These findings also have potential clinical implications, since combinations of various exercise and muscle training modalities with l ‐carnitine should be specifically targeted for the muscle groups to be trained.